Day-to-day and longitudinal variability of the equatorial electrojet as viewed from the Sun-synchronous CSES satellite - Yamazaki, Yosuke; Stolle, Claudia; Xiong, Chao; Alken, Patrick; Yang, Yanyan; Zhima, Zeren; Harding, Brian; Yan, Rui (Frontiers in Astronomy and Space Sciences, 2024)
The intensity of the equatorial electrojet (EEJ) derived from the magnetic field measurements by the China Seismo-Electromagnetic Satellite (CSES) is analyzed for the low solar activity period of July 2018–April 2022. The CSES spacecraft flies in a Sun-synchronous orbit, providing the first continuous satellite observations of the afternoon EEJ at a fixed local time at 2 p.m. The EEJ intensities from CSES and concurrent observations from the Swarm satellite mission show a good correlation, supporting the reliability of the CSES EEJ data. Spectral analysis of the CSES data reveals the presence of three distinct oscillatory components in the day-to-day variation of the afternoon EEJ: (1) an eastward-propagating 2–3-day oscillation with zonal wavenumber 1, (2) a westward-propagating 5–6-day oscillation with zonal wavenumber 1, and (3) a zonally-symmetric 14–15-day oscillation. These oscillations result from upward-propagating waves in the atmosphere. That is, the first two can be attributed to the ultra-fast Kelvin wave and quasi-6-day wave, respectively, while the latter is likely due to the atmospheric lunar tide. The CSES EEJ data are also compared with lower thermospheric wind measurements by the Michelson Interferometer for Global High-Resolution Thermospheric Imaging (MIGHTI) onboard the Ionospheric Connection Explorer (ICON). The results suggest that the EEJ intensity correlates negatively with the equatorial eastward wind at 100–115 km, consistent with earlier studies. Contributions of different tidal wind components to longitudinal structures of the EEJ are evaluated. A four-peak structure during July–September can be largely explained by the eastward-propagating diurnal tide with zonal wavenumber 3 (DE3), while a two- or three-peak structure during December–January is mainly due to the combined effect of DE3 and the eastward-propagating diurnal tide with zonal wavenumber 2 (DE2). Furthermore, the CSES EEJ data are compared with the electron density measurements from the Langmuir probe onboard CSES. There is a positive correlation between the EEJ intensity and in-situ electron densities at ∼510 km from the same orbit, reflecting the plasma fountain effect. The correlation tends to be higher in the summer hemisphere, which may be due to the meridional wind in the thermosphere.